Determinants of Income Smoothing Practices with Managerial Ownership Structure and Firm Size as Moderators - Lestari, Putu Diah; Purnamawati, I Gusti Ayu; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of profitability, dividend policy, financial leverage on income smoothing practices and the effect of moderating managerial ownership structure and firm size on the effect of profitability, dividend policy, financial leverage on income smoothing practices. The research design used causal quantitative. The population of this study were all manufacturing companies on the Indonesia Stock Exchange as many as 157 companies. The sampling technique used purposive sampling with a total sample of 30 companies. The data analysis technique used moderated regression analysis. The results show that (1) profitability had a significant negative effect on income smoothing practices, (2) dividend policy had a significant positive effect on income smoothing practices, (3) financial leverage had a significant positive effect on income smoothing practices, (4) managerial ownership structure strengthens the negative effect of profitability on income smoothing practices, (5) managerial ownership structure weakens the positive effect of dividend policy on income smoothing practices, (6) managerial ownership structure weakens the positive influence of financial leverage on income smoothing practices, (7) firm size weakens the negative effect of profitability on earnings smoothing practices. income smoothing, (8) firm size strengthens the positive effect of dividend policy on income smoothing practices, and (9) firm size strengthens the positive effect of financial leverage on income smoothing practices.